Answer:
Explanation:
(√2)^2 + (√5)^2 =
2 + 5 = 7
But that equals the hypotenuse squared. The actual value will be √7
======================
(√3)^2 + 4^2 =
3 + 16
19 But this equals the hypotenuse squared, so the answer is actually (√19 ) which isn't there. It might be a right triangle, but none of the answers match this one.
===========================
2^2 + (√5)^2 = 4 + 5 = 9
This is the square of the hypotenuse. √9 = 3 which is the last one.
===========================
(2)^2 + (2)^2 = 4 + 4 = 8
But the hypotenuse will be √8
==========================
1^2 + 2^2 = 1 + 4 = 5
The hypotenuse is √5